Probing DCV5T-Me for Organic Photovoltaics: A Comprehensive DFT and NEGF Study - Souraya Goumri-Said; Rachida Rahmani; Abdelkader Chouaih; Mohammed Benali Kanoun (Chemical Physics Impact)
This study presents a detailed computational analysis of the DCV5T-Me molecule to evaluate its potential for organic photovoltaic (OPV) applications. The optimized geometry demonstrates a stable donor-acceptor structure with well-aligned molecular orbitals conducive to charge transfer. Electronic structure calculations reveal a HOMO-LUMO energy gap of ∼1.89 eV, aligning with strong absorption in the visible and near-infrared regions, with a maximum absorption wavelength around 650 nm. Time-dependent density functional theory (TD-DFT) confirms significant intramolecular charge transfer excitations, characterized by high oscillator strengths and transition dipole moments. Transport property analysis highlights robust molecule-electrode coupling, facilitating efficient charge injection and tunneling through low-energy barrier flow. Molecular device simulations show high current densities under applied bias, indicating efficient charge transport through the molecular junction. These results suggest that DCV5T-Me possesses the structural and electronic attributes necessary for high-power conversion efficiency, making it a competitive candidate for next-generation non-fullerene OPV devices.